Functional health efflciency in the city of Qurna - Murtadha Mudhefer Sahar Al-Kaabi / Ibraheem Hachem Lazim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The health of the individual constitutes the primary goal of all human societies, as it is the effective factor for the survival of the individual, a vital, productive element capable of carrying out his economic and social activity in an efficient manner that secures the survival and development of his life and ensures the advancement and progress of the society in which he lives. And health planning is the organizational means for developing "curative and preventive" health care programs at all levels. It is also an effective means of coordinating health services, leading to the achievement of goals with high efficiency. The research aims to clarify the reality of the spatial distribution of health institutions in the city of Qurna with a statement of the factors contributing to their distribution, as well as measuring the efficiency of health services based on local planning standards and the standards of the World Health Organization in evaluating the level of health services, One of the most important findings of the research is the extent of the shortage in the number of health institutions as well as their cadres, and this requires a serious pause by planners and decision-makers and an awareness of the responsibility entrusted to the them in studying the health situation and developing health plans for services, which have become a cornerstone in the economics of Countries